Indonesia-ASEAN Partnership to Counter-Terrorism in Indonesia - Yeyen Subandi; Hafidz Ridha Try Sjahputra; Muhammad Subhan (PT FORMOSA CENDEKIA GLOBAL, 2023)
Terrorism is an extraordinary crime whose impact is very detrimental to all humans who are victims of this crime. Indonesia, as a member country of the Association of Southeast Asia Nations (ASEAN), is one of the countries that have received several terrorist attacks, such as the Bali Bombing I in 2002, the JW Marriot Bombing in 2003, the Bali II Bombing in 2005, the JW Marriot and Ritz Carlton Bombings in 2005 and 2009, and lately the terrorist attack that happened in Surabaya in 2018. This article aims to examine and analyze the cooperation between ASEAN and Indonesia and the mutual benefits and challenges of Indonesia-ASEAN cooperation from time to time. Furthermore, the study also examines the challenges and opportunities ahead from both sides and explores new strategies to overcome the challenges ahead and find ways to adapt to the terrorist modus operandi, which is constantly evolving from time to time to maintain stability in ASEAN. This study used the theory of international organizations and international regimes alongside bibliometric analysis methods with VOSviewer software as the theory and tool to analyze the topic.